The Effect of Dividends, Debt-to-Equity Ratio, and Firm Size on Firm Value: A Case Study of PT. Unilever Indonesia from 2014 to 2023 - Yusnita, Ida (The Future of Education Journal, 2025)
This research aims to analyze the influence of dividends, debt to equity ratio (DER), and company size on company value at PT Unilever Indonesia during the 2014-2023 period. The main issues raised in this research include the relationship between dividend policy, capital structure (DER), and company scale or size in increasing company value as reflected in share prices. This research uses a quantitative approach with multiple linear regression analysis methods. The data used is secondary data in the form of PT Unilever Indonesia's financial reports during the research period. The independent variables in this research are dividends, debt to equity ratio, and company size, while the dependent variable is company value as measured by the ratio of market price to book value. The research results show that dividends and company size have a significant positive effect on company value, while the debt to equity ratio does not have a significant effect on company value.